Perception of the Church in Lagos Mainland on Contemporary Family and Responsible Parenting in Lagos State, Nigeria (Global Journal of Human-Social Science, 2015)
The study examined the perceptions of people about contemporary family and responsible parenting using a descriptive survey design. The opinions of two hundred randomly selected participants made up of one hundred (100) males and one hundred (100) females were analyzed using frequency counts and percentages. A total of four churches from the mainland area of Lagos State was the population of the study. Four research questions were raised. Findings indicated that more of the respondents are in support of introducing courtship into the marriage institution. 100% of the respondents agree that the husband is the head of the family. Respondents also indicated their opinions about responsible parenting. 100% disagree that the husband's career is more important than the family. They also agree that they will allow their children marry from other tribes. 90% agreed, while 10% disagreed. The respondents also indicated their opinion on same-sex-marriage. 100% will not recognize or permit this. Discussions were drawn from the findings, and recommendations were made. It was recommended that the sanctity of the marriage institution be upheld and the children brought up by both parents.
Keywords: church; contemporary family; lagos mainland; responsible parenting; perception